(untitled) (European Journal of Health Research, 2020)
The role of muscle strength in the performance of activities of daily living and exercise, as well as in the prevention of chronic diseases, is increasingly recognized. The objective of this study was to analyze the strength levels of the upper limbs with the quality of life in the European population over 65 years. 419 elderly people (69.12 ± 9.19 years) were recruited from different European countries (Bulgaria, Spain, Hungary, Italy and Portugal), belonging to the European project IN COMMON SPORTS Erasmus Plus. The strength of the upper limbs was assessed by means of the Handgrip of both arms and the quality of life through the EuroQol-5D test (EQ-5D). A descriptive analysis and a Pearson correlation was performed. The results show an inverse relationship between quality of life and higher train strength, that is, higher values of higher train force are related to better quality of life for the European population over 65 years.